Oral Mucosal In Vitro Cell Culture Model to Study the Effect of Fructilactobacillus Phage on the Interplay between Food Components and Oral Microbiota - Ghadimi, Darab; Ebsen, Michael; Röcken, Christoph; Fölster-Holst, Regina; Groessner-Schreiber, Birte; Dörfer, Christof; Bockelmann, Wilhelm (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background and Aims: Dietary habits, food, and nutrition-associated oral dysbiosis lead to the formation of microbial biofilm, which affects the overall health of an individual by promoting systemic diseases like cardiovascular disease, immunological disorders, and diabetes. Today's diets contain a variety of fermentable carbohydrates, including highly processed starch and novel synthetic carbohydrates such as oligofructose, sucralose, and glucose polymers. These constitute risk factors in the initiation and progression of oral dysbiosis. Oral, lung and gut microbiomes are interlinked with each other via direct and indirect ways. It is unknown whether or not lactobacilli and Lactobacillus phages are able to rescue dysbiotic effects by decreasing the uptake into the cells of excess simple sugars and their derivatives present within the digestive tract. Materials and Methods: Using transwell cell culture plate inserts, six groups of in vitro co-cultured TR146 and HepG2 cells, grown in DMEM medium either with or without sucrose (10 % v/v), were treated with 1) PBS, 2) Fructilactobacillus sanfranciscensis (F.s) H2A, 3) F.s H2A and sucrose, 4) F.s H2A plus sucrose plus phage EV3 lysate, 5) F.s H2A plus sucrose plus phage EV3 supernatant, and 6) F.s H2A plus sucrose plus phage EV3 particles. The pH of the culture medium (indicating lactic acid production) and key oral biomarkers, including cytokines (IL-1β and IL-6), inflammatory chemokines (e.g., CXCL8 and CCL2), and homeostatic chemokines (e.g., CXCL4 and CCL18) were measured. Results: Excess sucrose significantly enhanced inflammatory signal molecules (e.g., IL-1β, IL-6, and CCL2) secretion, concomitant with the enhancement of intracellular triglycerides in co-cultured HepG2 cells. Co-culture with F.s H2A decreased the sucrose-induced release of inflammatory signal molecules from co-cultured cells, these effects being abolished by F.s phage EV3. Conclusion: This study shows that Lactobacillus phages apparently influence the interplay between food components, oral microbiota, and the oral cellular milieu, at least in part by affecting the microbial uptake of excess free simple sugars from the oral milieu. To confirm the biological consequences of these effects on human oral microbiota and health, further studies are warranted, incorporating ex vivo studies of human dental plaque biofilms and host biomarkers, such as cytohistological, molecular, or biochemical measurements.
Keywords: high-sugar diets